STUDI MENGENAI PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN NASABAH UNTUK MENINGKATKAN LOYALITAS (Studi pada Nasabah Tabungan Bank CIMB Niaga Pemuda Semarang) - Korn, Henry Alphonse (Master of Management Diponegoro University, 2013)
In early development, the concept of customer loyalty is synonymous with customer satisfaction.In banking, there is a tendency that satisfied customers will be loyal to the bank. However, inthe deeper viewed over the customer satisfaction tends to be higher than loyalty, so customersatisfaction will not necessary to loyal to the bank because there are other things that affectloyalty.This research was aimed to examine the effect of the variable quality of service and productquality to customer satisfaction and customer loyalty. Inferential analysis was done by usinganalysis of Structural Equation Modeling (SEM) Amos 16.0.The test results of SEM analysis showed that the quality of service significantly proved influenceon customer satisfaction, product quality proved a significant effect on customer satisfaction,and customer satisfaction proved significant effect on customer loyalty.